The correlation between interleukin-6 levels and quality of life in late-stage breast cancer patients with anxiety syndrome at Haji Adam Malik General Hospital, Medan - Ella Yunita Daulay; Mustafa Mahmud Amin; Elmeida Effendy; Vita Camellia; Kamal Basri Siregar (Medicinski glasnik, 2026)
Aim: Breast cancer is the most common cancer found in women including in Indonesia. Breast cancer patients are prone to have anxiety and it affects their quality of life. Interleukin-6 (IL-6) is one of the pro-tumorigenic cytokines that increases in breast cancer and is associated with worse prognosis and cancer metastasis. Several studies demonstrated the correlation between inflammatory cytokines and anxiety disorders. Therefore, this study aimed to determine the correlation between IL-6 and quality of life with anxiety syndrome in patients with late-stage breast cancer. Method: This cross-sectional study involved women with late-stage breast cancer (Stage III and IV) in Haji Adam Malik General Hospital. IL-6 levels were assessed using Sandwich enzyme-linked immunosorbent assay (Sandwich-ELISA). The quality of life and anxiety syndromes were assessed using the European Organization for Research and Treatment of Cancer 30-Item Quality of Life Questionnaire (EORTC QLQ-C30) and Hospital Anxiety and Depression Scale (HADS)-A questionnaire, respectively. Kruskal-Wallis test was used to determine the correlation between variables. A p-value < 0.05 was considered statistically significant. Result: Fifty-nine women met the inclusion criteria. The analysis demonstrated that higher IL-6 levels (p < 0.001) and poor QoL (p < 0.001) were related to severe anxiety disorders in late-stage breast cancer patients. Conclusion: IL-6 level and quality of life were potentially used in the risk stratification and early detection of anxiety syndrome in late-stage breast cancer cases.
Keywords: anxiety; Breadt neoplasm; cytokine; quality of life